Image retrieval behavior of medical students - Mona Kamali; Hasan Ashrafi-rizi; Mina Afshar (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The first step to properly designing image retrieval systems with the aim of meeting the needs of students and researchers is to be fully aware of their behavior in the face of these systems and image resources. The purpose of this study is to identify image retrieval behavior of medical students. MATERIALS AND METHODS: This study is an applied research that has been done by descriptive-survey method. The statistical population of this study is 816 general (clinical) medical students who are studying in the fourth and fifth years. Using Morgan and Krejcie table, the number of statistical sample members was 265 who were selected using random sampling method. Research data have been gathered using a questionnaire (researcher made) and then analyzed using SPSS22 software. RESULTS: The findings showed that 78.1% of students consider the use of images in class presentations or scientific reporting as the most important reason. According to 73.6% of respondents, the highest rate of image search is in the form of videos. About 76.2% of them consider general search engines to be the most common source for receiving images. For this purpose, only 3.8% of students refer to the librarians. Among the databases from which medical images can be obtained, the most well-known source was the Springer website, which 30.6% of respondents were familiar. CONCLUSION: The process of meeting the image-seeking needs is influenced by various individual, social, and other factors. This study can improve this process by providing the necessary suggestions to medical students, for eliminating barriers and problems in accessing reliable resources and visual information they require, to clarify the necessity of promoting technical knowledge to search accurately and to help for finding solutions to medical and treatment educational centers to have access to reliable and up-to-date information.